Public relations ethics : the real-world guide - Morris, Trevor; Goldsworthy, Simon (Routledge, 2021)
"This book is a pragmatic, case-rich guide to how current and future public relations professionals can apply ethical principles and the industry's codes of ethics to their day-to-day work. Authors Trevor Morris and Simon Goldsworthy draw on their years of industry experience to illustrate key ethical issues and ground them in reality, all with an international frame of reference. The book incorporates interviews with industry practitioners, frequently offering dueling perspectives, as well as recent examples of real-life complaints and disciplinary issues. Provocative questions and exercises help readers grapple with ethical dilemmas and review the key scenarios and challenges that professionals face. The book is ideal at the undergraduate, postgraduate, and continuing education level as a core text for public relations ethics courses and a supplementary text for general public relations survey courses. Accompanying the text are online resources for both students and instructors, including lecture slides and links to further resources"--